Distinctive diamagnetic fabrics in dolostones evolved at fault cores, the Dead Sea Transform. (August 2015) - Braun, D.; Weinberger, R.; Eyal, Y.; Feinstein, S.; Harlavan, Y.; Levi, T.
Abstract: We resolve the anisotropy of magnetic susceptibility (AMS) axes along fault planes, cores and damage zones in rocks that crop out next to the Dead Sea Transform (DST) plate boundary. We measured 261 samples of mainly diamagnetic dolostones that were collected from 15 stations. To test the possible effect of the iron content on the AMS we analyzed the Fe concentrations of the samples in different rock phases. Dolostones with mean magnetic susceptibility value lower than −4 × 10 −6 SI and iron content less than ∼1000 ppm are suitable for diamagnetic AMS-based strain analysis. The dolostones along fault planes display AMS fabrics that significantly deviate from the primary "sedimentary fabric". The characteristics of these fabrics include well-grouped, sub-horizontal, minimum principal AMS axes ( k 3 ) and sub-vertical magnetic foliations commonly defined by maximum and intermediate principal AMS axes ( k 1 and k 2 axes, respectively). These fabrics are distinctive along fault planes located tens of kilometers apart, with strikes ranging between NNW-SSE and NNE-SSW and different senses of motion. The obtained magnetic foliations ( k 1 – k 2 ) are sub-parallel (within ∼20°) to the fault planes. Based on rock magnetic and geochemical analyses, we interpret the AMS fabrics as the product of both shape and crystallographic anisotropy of the dolostones. Preferred shape alignment evolves due to mechanical rotation of subordinate particles and rock fragments at the fault core. Preferred crystallographic orientation results from elevated frictional heating (>300 °C) during faulting, which enhances c-axes alignment in the cement-supported dolomite breccia due to crystal-plastic processes. The penetrative deformation within fault zones resulted from the local, fault-related strain field and does not reflect the regional strain field. The analyzed AMS fabrics together with fault-plane kinematics provide valuable information on faulting characteristics in the uppermost crust. Graphical abstract: Highlights: Dolostones with iron content <1000 ppm are controlled by the diamagnetic phase and suitable for AMS-based strain analysis. Diamagnetic fabrics of dolostone fault cores display foliations (k1–k2) that are sub-parallel to fault planes. Fabrics within fault zones resulted from fault-related local strain and are associated with plastic and brittle deformation.